PENGARUH REMUNERASI TERHADAP MOTIVASI DALAM PELAYANAN PUBLIK (Studi pada kantor Kejaksaan Tinggi Aceh) - Iqbal Mukhti (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The purpose of this study was to look at the influence of remuneration on employee motivation High Prosecutor's Office in Aceh. Data used in this study are primary data using techniques of data collection through the distribution of questionnaires to respondents. Results of research can be concluded is based on the results of data processing using SPSS.v.22.0 program. show the whole statement is valid because it has a significance level below 5%. Whereas if done manually, the correlation value is obtained each statement should be compared with the critical value product moment correlation where the results showed that all the statements have correlation values above the critical value of 5% indicates output reliability testing with Cronbach alpha of the 15 questions have been answered respondents , it can be seen that the alpha to variable remuneration (X) = 0.759 and Public Service Motivation (Y) = 0.900. So that the research results are statistical equations Y = 1.107 + 0.789 x. Keywords—Remuneration, Motivation, Public Service